(untitled) (Research, Society and Development, 2020)
This text presents the initial results of a research attentive to the trajectory of the teacher, journalist and cultual activist Maria Mariá de Castro Sarmento, focusing, above all, on the foundation of the public library of a city in the interior of Alagoas: União dos Palmares. The indicated time frame corresponds to the years that date the publications that the máster had made on the theme indicated, specifically in the Jornal de Alagoas (1953-1954). New History guidelines are considered, from the choice of object to the selection and use of sources. The latter being newspapers, for a long time invisible in historiography. Given the specificities, the interference of the foundation of libraries in the process of training readers is analyzed in the period marked by the attempt to redemocratize Brazil recently freed from the dictatorship of the Estado Novo. The claims for the implantation of such institutions began in the 1930s, with the participation of Amanda Álvaro Alberto and Cecília Meireles, due to the interference of the pragmatic educational conception defended by Escola Nova, and the light of other philosophical-pedagogical interferences born in the 1950s is reinvented. The educator who inspires this study, places herself as a character who, in the face of the peculiar intellectual anxiety, had been forgotten by traditional historiography.